EVALUASI PROGRAM GERAKAN LITERASI SEKOLAH KELAS V DI SD NEGERI MANDUANG - Ni Putu Sri Ratih Sugiantari; Nurul Isnaini Fitriyana; I Wayan Nurmertayasa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to evaluate the implementation of the School Literacy Movement (GLS) in fifth-grade students at Manduang State Elementary School, which includes the familiarization, development, and learning stages. The study used a qualitative approach with an evaluative approach. Data were collected through observation, interviews, and documentation, then analyzed descriptively. The results showed that the implementation of the GLS in the familiarization stage was optimal, including a 15-minute reading session before class, the use of non-textbooks, and the use of a reading corner. In the reinforcement stage, students were able to participate in reading discussions, retell readings, and write reflections, although some students' involvement still needed to be improved. In the learning stage, literacy was integrated into the learning process through reading, understanding, analyzing, writing, and communicating information from reading. Obstacles that were still encountered included low participation among some students, uneven reading comprehension and critical thinking skills, and the need for support in communication skills. Overall, the implementation of these activities in fifth-grade students at Manduang State Elementary School was successful and supported the development of students' literacy potential. However, ongoing guidance is still needed for optimal implementation.